Fiber Composition of the Grasscutter (Thryonomys swinderianus, Temminck 1827) Thigh Muscle: An Enzyme-histochemical Study - Bakou, Serge Niangoran (J Cytol Histol, 2015)
The aim of this study was to describe de fiber composition in the thigh muscles of grass cutter (Thryonomys swinderianus, Temminck 1827). Ten 4 to 6-month-old (3 to 4 kg) male grasscutter were used in this study. Eleven skeletal muscles of the thigh [M. biceps femoris (BF), M. rectus femoris (RF), M. vastus lateralis (VL), M. vastus medialis (VM), M. tensor fasciae latae (TFL), M. semitendinosus (ST), M. semimembranosus (SM), M. semimembranosus accessorius (SMA), M. Sartorius (SRT), M. pectineus (PCT), M. adductor magnus (AM)] were collected after animals euthanasia and examined by light microscopy. Three muscle fiber types (I, IIB and IIA) were found in these muscles using enzyme histochemical techniques [myosine adenosine triphosphatase (ATPase) and nicotinamide adenine dinucleotide tetrazolium reductase (NADH-TR)]. Ten of these eleven muscles are composed by 89% to 100% of fast contracting fibers (types IIA and IIB), while the SMA was almost exclusively formed by slow contracting fibers.